A study on the efficacy of hot vegetable oil as treatment for dentinal hypersensitivity - Capule, Ma. Angela P.
Commercially available 100% pure polyunsaturated corn oil was investigated as to its effect on sensitive cervical areas of teeth. Twenty seven subjects were tested for responses to tactile, cold, hot, and electric pulp testing methods; the results of which served as baseline data. Bilateral cervical lesions were then treated with the test substance (vegetable oil on the right) and the control (NSS on the left). Both substances were heated uniformly before application. The same four tests were conducted after seven consecutive days of application of both the oil and the NSS. The results indicated that hot vegetable oil showed a significant effect in reducing dentinal hypersensitivity as compared to NSS.